Patterns of Delaying Surgery for Breast Cancer During the COVID-19 Outbreak in Daegu, South Korea - Lee, Jeeyeon; Jung, Jin Hyang; Kim, Wan Wook; Park, Chan Sub; Park, Ho Yong (Frontiers in Surgery, 2020)
Background: The coronavirus disease 2019 (COVID-19) outbreak in South Korea has affected the diagnosis, treatment, and follow-up protocols of various cancers. This study investigated the patterns of delaying surgery for breast cancer during the COVID-19 outbreak in South Korea and evaluated factors that may have affected the decision to delay surgery. Methods: From February 18 to April 18, 2020, which was the critical period for COVID-19 in South Korea, patients with breast cancer who were scheduled for surgery were evaluated in terms of their decision in delaying the procedure. The patients were divided into two groups: delaying and non-delaying surgery groups. The association between personal and clinicopathological factors and delaying surgery was evaluated. Results: In patients belonging to the delaying surgery group, the mean delay period was 15.9 (standard deviation [SD], ±10.9) days. Patients in the non-delaying surgery group were relatively younger (p = 0.003), single (p = 0.038), had planned mastectomy (p = 0.041), received needle biopsy for diagnosis (p = 0.021), and had a higher clinical N stage (p = 0.049) and multifocal lesions of breast cancer (p = 0.020). However, there were no significant differences in terms of the pathological T and N stages between the two groups. Conclusion: During the COVID-19 outbreak, there was no occurrence of nosocomial infection in the non-delaying surgery group and no statistical difference in pathological stage between the delaying and non-delaying surgery groups. Although patients in the delaying surgery group tended to be relatively older, married, and had planned small-scale surgery with a good prognosis of breast cancer, the prognosis did not appear to have changed whether delaying or proceeding with surgery for breast cancer during the COVID-19 outbreak.